2005
DOI: 10.1021/bm049419y
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-Producing Polyurethanes

Abstract: Thrombus formation and eventual intimal hyperplasia are the leading causes of small-diameter synthetic vascular graft failure. To combat these issues, we have incorporated a diazeniumdiolate-modified nitric oxide (NO)-producing peptide into a polyurethane to improve the thromboresistance of this biocompatible polymer. NO production by polyurethane films occurred for approximately 2 months under physiological conditions, and mechanical properties of the material were suitable for vascular graft applications. Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 35 publications
2
91
0
1
Order By: Relevance
“…55,56 We have previously shown that the addition of an NO-releasing peptide into the main chain of a polyurethane can improve thromboresistance while increasing endothelial cell proliferation, while retaining the mechanical properties of commercially available vascular graft materials. 52 Prior studies have also shown that the addition of a cell adhesion peptide and PEG into a biocompatible polyurethaneurea encourages endothelial cell adhesion to the polymer surface while decreasing platelet adhesion. 15,28 In this study, we have successfully combined the effects of NO, PEG, and the cell-adhesive peptide YIGSR to further reduce platelet adhesion and encourage endothelialization of polyurethane, enhancing its performance as a candidate material for smalldiameter vascular substitutes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…55,56 We have previously shown that the addition of an NO-releasing peptide into the main chain of a polyurethane can improve thromboresistance while increasing endothelial cell proliferation, while retaining the mechanical properties of commercially available vascular graft materials. 52 Prior studies have also shown that the addition of a cell adhesion peptide and PEG into a biocompatible polyurethaneurea encourages endothelial cell adhesion to the polymer surface while decreasing platelet adhesion. 15,28 In this study, we have successfully combined the effects of NO, PEG, and the cell-adhesive peptide YIGSR to further reduce platelet adhesion and encourage endothelialization of polyurethane, enhancing its performance as a candidate material for smalldiameter vascular substitutes.…”
Section: Discussionmentioning
confidence: 99%
“…28 However, the addition of the peptides into the polymer backbone does increase mechanical strength. 28,52 Both the elastic modulus and tensile strength of PUBD-PEG-YIGSR-NO were slightly greater than those of PUBD-PEG-YIGSR (Figure 3). The mechanical properties of these materials were comparable to commercial polyurethane vascular grafts.…”
Section: Mechanical Propertiesmentioning
confidence: 95%
“…It has been indicated that NO-generating polyurethane may be suitable as a candidate material for diameter vascular grafts [63]. NO-releasing biopolymers had the potential to prolong vascular grafts without adverse systemic vasodilation in a sheep model [64].…”
Section: Discussionmentioning
confidence: 99%
“…54,55 This approach eliminates the need for reaction additives, thus avoiding leaching of undesired byproducts. Jun et al 54 showed that NO production by these polyurethane films occurred for Ϸ2 months under physiological conditions in vitro and that mechanical properties of the material were suitable for vascular graft applications. Furthermore, platelet adhesion was greatly diminished, vascular smooth muscle cell growth was inhibited, and endothelial cell growth was stimulated across the polyurethane graft.…”
Section: No Modificationsmentioning
confidence: 99%